Role of Bayer red mud and phosphogypsum in cement-stabilized dredged soil with different water and cement contents - Wan, Xing (2024)
Bayer Red mud (BRM) and phosphogypsum (PG) are known as two main industrial wastes around the world. Previous studies have demonstrated the contribution of BRM and PG in cement-based hydration reactions, but their collaborative role is still pending in cement-stabilized dredged soil. In this study, the collaborative role of BRM and PG was examined by comparing micro-macro properties of stabilized clay with different initial water contents, cement contents and BRM/PG proportions. The chemical and microscopic results are found highly complementary, indicating existence of alkali-activation effects, pore-filling effects and cementation damage effects in stabilized clay. The pH of 8% cement-stabilized clay increases by about 0.5 after addition of 10% alkaline BRM, which activates clay mineral in dredged soils and results in more sufficient pozzolanic reactions. In addition, the pore-filling effect of ettringite is much more contributory in soils with a higher water content of 140%. Such positive effects significantly weaken as the water content decreases to 80%, the cementation damage effects come into picture instead. The unconfined compressive strength (UCS) after 7 days curing nearly triples with an optimal proportion of BRM and PG, demonstrating effectiveness of the proposed approach. As the water and cement contents increase, the optimal proportion of BRM and PG evolves from R7.5P2.5 into R5P5.